Therapeutic potential of curcuminoids in the treatment of selected autoimmune diseases - Joanna Cieszkowska; Karina Otręba; Karolina Czupryńska; Piotr Daniel; Michał Leśkiewicz; Justyna Aleksandra Składanek (Kazimierz Wielki University, 2024)
Introduction The cause of autoimmune diseases is often unknown. Continuous research into the mechanism of these diseases allows us to discover new metabolic pathways, and thus new potential drugs that may become promising therapeutic tools in the future. Alternative methods of treatment are increasingly used when standard therapy does not bring the intended effects. One of the alternative methods of treatment is turmeric contained in Curcuma longa L. Aim of the study The aim of this article was to present the extremely promising potential of turmeric in the treatment of autoimmune diseases. Materials and methods The article is the result of a review of recent scientific literature using PubMed, Scopus and Google Scholar databases. The literature was reviewed using the keywords. Results In recent years, research on turmeric has accelerated significantly. Due to the insufficient effects of therapy achieved with standard methods of treatment, researchers want to find a new agent to fight serious diseases. Currently available medical literature has confirmed the beneficial effects of turmeric on inflammation in the body. The very mild side effect profile is also worth noting. Conclusions The anti-inflammatory effect obtained after the administration of appropriate doses of turmeric requires further research before it can be registered as one of the preparations for the treatment of autoimmune diseases. However, this topic is very interesting, and the substance itself is very interesting in the context of future disease therapy.